The influence of alloy elements in Ti6Al4V and Ti35Nb2Ta3Zr on the structure, morphology and properties of MAO coatings. (November 2018) - Wang, Chaohu; Ma, Fengcang; Liu, Ping; Chen, Juan; Liu, Xinkuan; Zhang, Ke; Li, Wei; Han, Qingyou
Abstract: In this work, pure titanium, Ti6Al4V and Ti35Nb2Ta3Zr alloy treated in electrolyte of sodium silicate in the method of micro-arc oxidation were systematically studied. The results indicate that Ti35Nb2Ta3Zr alloy has better film-forming property for that a nested membrane with a porous structure formed on its cover. And the relative content of anatase phase with biological activity is much more than that of the rutile phase as compare to pure Ti and Ti6Al4V, which can effectively improve the deposition capacity of apatite. Furthermore, Ti35Nb2Ta3Zr after micro-arc oxidation (MAO) treatment has excellent corrosion resistance due to its denser and thicker films, as well as the formation of the passivation film owing to the existence of Nb2 O5 phase on the surface. The result of wetting angle test shows the coating of Ti35Nb2Ta3Zr owns long-lasting and excellent hydrophilic property. Highlights: The effects of different substrates on micro-arc oxidation are compared. The Ti35Nb2Ta3Zr alloy has better film-forming properties. The relative content of anatase phase with biological activity in Ti35Nb2Ta3Zr coating is the highest. The Ti35Nb2Ta3Zr coating has excellent corrosion resistance and long-lasting hydrophilic properties.